Holmvassdalen naturreservat – botanisk mangfold og kontinuitet i granskog - Lorås, Jostein; Eidissen, Siw Elin (Norsk Botanisk Forening, 2013)
This paper presents knowledge about the ecology and botanical biodiversity in Holmvassdalen naturereserve in yhe southern part of Nordland county. This area has a rich flora and funga connected to calcareous birch and spruce forests, and the number of botanical red-listed species is mote than 120. A number of nature types are represented in the area, of whicc several are red-listed. Furthermore, the article presentshistorical documentation concerning agrarian and sami land-use, as Holmvassdalen has been influenced by human activitiesfor a long time through cultivation, forestry and different grazing.A study shows that immigration of spruce happened regionally about one thousand years ago. As a consequence the first clusters of distribution may be twice as old. Besides, the logging history in the area emphasizes clearly that the forest has never been clearcut. An interesting result of these factors is a whole range of rare and highly specialized spevies of mycorrhiza fungi connected to calcareous spruce forest growing in the area. All in all, several factors indicate long time ecological continuity in Holmvassdalen nature reserve